Prescribing trend of tapentadol in a Sydney local health district. Issue 9 (7th July 2022) - Mirabella, Jennifer; Ravi, Deepa; Chiew, Angela L.; Buckley, Nicholas A.; Chan, Betty S.
Abstract : Aims: Tapentadol, an opioid with mu‐opioid receptor agonism and noradrenaline reuptake inhibition, has been increasingly used in Australia since 2011. However, data on hospital prescribing trends and indications are scarce. This study aimed to investigate hospital prescribing trends of tapentadol, oxycodone and tramadol in a Sydney local health district (LHD) and the indications for tapentadol hospital prescriptions in an Australian tertiary hospital. Methods: We analysed 5‐year patient dispensing for tapentadol, oxycodone and tramadol from four hospitals in a Sydney LHD with data expressed as oral morphine equivalents (OME). We also conducted a retrospective review of 140 and 54 patients prescribed tapentadol at a tertiary hospital's surgical and spinal units in 2020. Results: Over 5 years in the Sydney LHD, there was a 19.5% reduction in total dispensing of these opioids from 1 225 210 to 986 477.5 OME milligrams. Decreases were specifically for oxycodone (−37.8% immediate‐release, −65.2% sustained‐release) and tramadol (−74.6% immediate‐release, −70.1% sustained‐release). Contrastingly, hospital prescriptions of tapentadol immediate‐release increased by 223.2% between 2018–19 and 2020–21 while sustained‐release increased by 17.9% from 2016–17 to 2020–21. By 2020–21, tapentadol overtook oxycodone to become the most prescribed opioid in the Sydney LHD (51.4%). At the hospital's surgical units, 137 (97.9%) patients were prescribed tapentadol for acute post‐operative pain with the majority (54.0%) prescribed both immediate‐release and sustained‐release tapentadol, while 71.1% were prescribed for neuropathic pain in the spinal units. Conclusion: In a Sydney LHD, tapentadol prescriptions increased significantly to become the preferred opioid analgesic. At the hospital's surgical units, off‐label prescriptions of tapentadol sustained‐release for acute post‐operative pain were observed. Abstract :